THE ROLE OF INNOVATIVE ENTREPRENEURSHIP IN ENSURING THE ECONOMIC DEVELOPMENT OF UKRAINE IN THE POST-WAR PERIOD - ANHELKO, Iryna; SAMOTIY, Nataliya; LEKH, Halyna (Herald of Khmelnytskyi National University. Economic sciences, 2023)
The article highlights the role of innovative entrepreneurship in ensuring the economic development of Ukraine in the postwar period. The state of development of innovation processes in Ukraine is characterized through the prism of allocation of the main indicators of innovation activity of domestic business entities. On the basis of the assessment of the state of development of innovation processes in Ukraine, the key problems that affect the effective formation and functioning of domestic innovative entrepreneurship and the innovation system in general are allocated. The main advantages of innovative entrepreneurship are allocated. It is noted that innovative entrepreneurship affects the process of structural reorganization of the economy, acceleration of its growth, creation of an innovative and competitive environment and efficient use of available resources. At the same time, it is noted that the role of innovative entrepreneurship is extremely broad and important, since it affects the level of knowledge intensity and competitiveness of the national economy. It is emphasized that in modern economic conditions, small innovative enterprises play a key role in ensuring the effective development of the innovation system. It is determined that small innovative enterprises have a number of advantages over large companies. They are distinguished by high mobility, dynamism, sensitivity to the slightest changes in the market situation, the ability to respond quickly to consumer needs, new scientific ideas and solving specific problems related to obtaining the final result from the implementation of an innovative product. It is generalized that in the current economic environment, small innovative business entities need support from the State, which should be aimed at applying the achievements of scientific and technological development and innovation partnership.
Keywords: innovative entrepreneurship; innovative system; innovative development; economic development